2018
DOI: 10.32870/ap.v10n1.1149
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Flipped Classroom in a propaedeutic course of mathematical skill in high school

Abstract: Presentamos un estudio descriptivo con alcance cuantitativo cuyo objetivo es comprobar la efectividad del método de aula invertida como una estrategia tecnopedagógica para mejorar el rendimiento en la habilidad matemática en estudiantes aspirantes para ingresar al bachillerato. El diseño de esta investigación fue cuasiexperimental y participaron 101 estudiantes en dos grupos (control y experimental). Un pretest fue aplicado a ambos grupos sobre habilidad matemática antes de iniciar la intervención de la estrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…As part of their results, Veytia et al [17] indicate that the flipped classroom attracted students' attention through the use of videos recorded by teachers for understanding topics, and there was an increase in the number of students passing the subject, with 92% of 90 students who participated preferring the flipped classroom over traditional classes. However, in the case of Madrid et al [18] in mathematics, no significant changes were found compared to the traditional teaching methodology. Authors such as Aguilera et al [16] indicate that the flipped classroom can be applied in all curricular areas, as well as in primary, secondary, upper secondary, and higher education.…”
Section: Flipped Classroommentioning
confidence: 86%
See 1 more Smart Citation
“…As part of their results, Veytia et al [17] indicate that the flipped classroom attracted students' attention through the use of videos recorded by teachers for understanding topics, and there was an increase in the number of students passing the subject, with 92% of 90 students who participated preferring the flipped classroom over traditional classes. However, in the case of Madrid et al [18] in mathematics, no significant changes were found compared to the traditional teaching methodology. Authors such as Aguilera et al [16] indicate that the flipped classroom can be applied in all curricular areas, as well as in primary, secondary, upper secondary, and higher education.…”
Section: Flipped Classroommentioning
confidence: 86%
“…It is essential to highlight that in the flipped classroom "what matters is not what students know, but what they are capable of doing or solving with their knowledge through practical experiences" (p. 131) [14]. Examples of the implementation of this methodology in upper secondary education include studies by Veytia et al [17] and Madrid et al [18], which demonstrate its development in informatics and mathematics subjects, respectively. As part of their results, Veytia et al [17] indicate that the flipped classroom attracted students' attention through the use of videos recorded by teachers for understanding topics, and there was an increase in the number of students passing the subject, with 92% of 90 students who participated preferring the flipped classroom over traditional classes.…”
Section: Flipped Classroommentioning
confidence: 99%
“…A pesar de esto, es importante señalar que en general la literatura científica muestra discrepancias significativas sobre el impacto del FC en el logro de aprendizaje o rendimiento académico, ya que aunque en numerosos estudios se reportan mejoras significativas en calificaciones y niveles de motivación, y una alta tasa de aceptación del FC en el alumnado (Veytia et al, 2019;Gaviria et al, 2019;Basso et al, 2018;Akçayır & Akçayır, 2018;Lo et al, 2018), en otros se afirma no haber encontrado diferencias significativas en los resultados de rendimiento al usar dicho enforque con relación a los obtenidos en clases tradicionales (Madrid-García et al, 2018;Scott et al, 2016;Clark, 2015).…”
Section: Discussionunclassified
“…Para continuar con la propuesta, se procedió a gestionar el permiso ante las autoridades pertinentes; se trabajó el diseño del aula en línea para presentar el material de estudio; se eligió la plataforma Google Classroom para compartir archivos, videos y otros materiales de manera gratuita. Además, como base para la aplicación del método aula invertida, se consideró la propuesta de Kim et al (2014) citado por (Madrid et al, 2018), centrado en la implementación de esta metodología. Después se procedió a la ejecución de la metodología siguiendo seis etapas: Diagnóstico (1), Capacitación (2), Selección de la asignatura o componente curricular, contenidos y las actividades de aprendizaje (3), Producción de materiales didácticos (4), Desarrollo de las actividades para implementar el aula invertida (5) y Cierre (6).…”
Section: Materiales Y Métodosunclassified